2022
DOI: 10.1186/s13049-022-01013-5
|View full text |Cite
|
Sign up to set email alerts
|

Standardised data collection in prehospital critical care: a comparison of medical problem categories and discharge diagnoses

Abstract: Background Prehospital medical problem reporting is essential in the management of helicopter emergency medical services (HEMS) operations. The consensus-based template for reporting and documenting in physician-staffed prehospital services exists and the classification of medical problems presented in the template is widely used in research and quality improvement. However, validation of the reported prehospital medical problem is lacking. This study aimed to describe the in-hospital diagnoses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Patients classified as ‘other’ were estimated to have an NNT of 25, informed by FHDB and expert judgment, reflecting the similar intensity of life support to trauma and intubation group. Due to the heterogeneity of patient groups [ 11 ], it is impossible to obtain exact information from this group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients classified as ‘other’ were estimated to have an NNT of 25, informed by FHDB and expert judgment, reflecting the similar intensity of life support to trauma and intubation group. Due to the heterogeneity of patient groups [ 11 ], it is impossible to obtain exact information from this group.…”
Section: Resultsmentioning
confidence: 99%
“…The patient demographics of the Finnish HEMS system has been assessed in a recent study [ 11 ]. We identified the primary groups of patients that comprise the majority of those assisted by HEMS, with evidence suggesting these groups either gain medical or logistical support from HEMS.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers in Scandinavia have demonstrated the feasibility of gathering detailed and comprehensive data nation-wide on all HEMS missions and treated patients using centralized and bespoke databases and data entry templates [ 55 57 ]. They also indicated that a national database is an important data source for research and quality improvement and could provide valuable insights into where HEMS operations could be improved [ 55 57 ]. Similarly, Greater Sydney Area HEMS described the long-term effectiveness of their airway registry on the completeness of documentation of prehospital rapid sequence intubation [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are well documented challenges associated with conducting prehospital and transport medicine research, including the extensive clinical, ethical, and logistical factors limiting clinical trials and accurate data collection and the inherent heterogeneity of the patient populations and systems that allow for generalization of results. [ 57 , 59 ].…”
Section: Resultsmentioning
confidence: 99%